Sosialisasi Energi Terbarukan dan Pelatihan Perakitan Listrik Tenaga Surya pada Siswa Sekolah Alam Le Cendekia Gowa - Muhammad Syahid; Jalaluddin .; Andi Amijoyo Mochtar; Gerard Antonini Duma; Rudi Amme; Lukman Kasim; Muh. Arjun (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2024)
Renewable energy is energy that comes from renewable energy sources. Renewable energy sources are energy sources that can be used indefinitely and will never run out because they can be recovered in a relatively short time, including geothermal, wind, bioenergy, sunlight, water flows and waterfalls, as well as movements and temperature differences in ocean layers.” Solar panels are the main equipment in a solar power generation system which functions to convert sunlight energy into electrical energy directly. Nowadays, human dependence on energy concerns almost all aspects of life. Energy reserves originating from fossil fuels throughout the world are estimated to only be up to 40 years for petroleum, 60 years for natural gas, and 200 years for coal. The condition of limited energy sources in the midst of increasing world energy needs from year to year (energy consumption growth in 2004 alone was 4.3 percent), as well as to protect the earth from global warming and environmental pollution makes the demand for immediate realization of new technology for renewable energy sources. Therefore, the Community Service Team of the Department of Mechanical Engineering, Faculty of Engineering, Hasanuddin University held community service at the LE CENDEKIA Nature School on December 14 2023. The aim of this service is to increase understanding regarding renewable energy and carry out simple applications of renewable energy for students. The method of implementing the service is by interview on the importance of renewable energy and training in solar power assembly. There were 25 socialization and training participants. Community service results show an increase in understanding of the importance of renewable energy from 20% to 50%, and knowledge about solar power assembly from 5% to 45%.